RAPID DETECTION OF WHITE SPOT SYNDROME VIRUS (WSSV) OF PENAEUS MONODON BY LATEX AGGLUTINATION TEST USING MONOCLONAL ANTIBODIES - Makesh, M.; Koteeswaran, A.; Chandran, N. Daniel Joy; Manohar, B. Murali; Ramasamy, V.; Chandramohan, A.; Raman, R. P.; Mukherjee, S. C. (Journal of Indian Fisheries Association, 2006)
Latex beads were sensitized with monoclonal antibodies (!\'lAb) raisedagainst VP28 of WSSV. The optimum concentration of l\1Ab required tosensitize the latex beads was 125 J.Ig/ml. The sensitized latex beads ,were used todetect WSSV from PCR-positive stomach tissue homogenates obtained frominfected shrimp. Stomach tissue homogenates from \VSSV-infected shrimpagglutinated the sensitized latex beads within I 0 minutes, while uninfectedsamples did not produce any agglutination, although non-specificagglutinations were observed in some samples. The analytical sensitivity,analytical specificity, diagnostic sensitivity and diagnostic specificity of the(LAT) agglutination test were assessed. The analytical sensitivity of the testwas 40 ng of purified WSSV (2 J.Iglml). The sensitized latex beads did notagglutinate with normal shrimp tissue or MBV-infected tissue homogenate.The test has a diagnostic sensitivity of 70 and 45o/o, respectively, compared tosingle-step and nested PCR. The diagnostic specificity of the test was 824%. Thistest is a simple and rapid on-farm test which can be used to corroborate clinicalsigns for the detection ofWSSVin grow-out ponds.Keywords: PenaerL-,' monodon, white spot syndrome virus, monoclonalantibodies, latex agglutination test